Legal consequences of adopting children of Indonesian citizens by foreign nationals - Fadilla Dwi Lailawati; Ferry Anggriawan; Sunarjo Sunarjo; Ariyanti Ariyanti; Mohammad Fahrial Amrulla (Jurnal Cakrawala Hukum, 2022)
This study aims to analyze the legal regulations regarding the adoption of children of Indonesian citizens by foreign nationals through a court decision process because in this case, the adoption is not a dispute which is then made into a decision, in accordance with the HIR stating that the decision was taken because of a lawsuit. This means that there must be a dispute between the disputing parties. Government Regulation 54 of 2007 concerning the Adoption of Children, contradicts article 184 HIR and needs to be reviewed because this regulation conflicts with the Criminal Procedure Code. Civil evidence is determined by very restrictive evidence, namely the judge in considering his decision is very fixated on the existing evidence. In this case, formal evidence is an authentic letter, namely a letter issued by an authorized agency made by an official who has been sworn in for an act. However, the letter may become inauthentic if a court decision overturns it; as long as there is no cancellation, the judge is bound by an authentic letter because the evidence is perfect evidence, so if the decision to adopt a child becomes void if there is a court decision that cancels it.How to cite item: Aisyiah, C., Wisnuwardhani, D. (2022). Notary, public official or public official: implications for the position of notary. Jurnal Cakrawala Hukum, 13(3), 242-252. DOI:https://doi.org/10.26905/idjch.v13i3.9012.